Fatores de avaliação de marca: um estudo experimental no mercado de luxo - Pizzinatto, Andrea Kassouf (2013)
This study approaches the country of origin effect and endorser as influence factors in brand evaluation, specifically for luxury market. The use of endorsers in advertisements has been widely used for manager goals and subject of academic investigation. The country of origin effect has been largely studied, whose theory is based in the positive and negative stereotype developed in the mind of the consumer, about the country and how it influences the evaluation of product produced in this country. The methodology of the study involved two experiments: for the first one, whose subject was endorser, it was elaborated advertisements for luxury brands and non-luxury brands and the effect was evaluated in three different situations such as without endorsers; celebrity endorser and non-famous endorser. For the experiments of country of origin effect it was developed advertisements for three situations: the negative country of origin effect, it means a country that has a stereotype for bad manufacture quality; other country with positive country of origin effect, or which has stereotype of good quality for manufacture; finally the last advertisement did not mention the country of origin. The data analysis plan for both experiments involved paper questionnaire for a sample of 631. The procedure was made by means comparisons, univariate variance analysis, ANOVA, with the software SPSS. The results indicated that the utilization of endorser has no significant effect in the luxury brands; they have self-enforcement, but have more significant effect in non-luxury brand advertisements. Regarding the country of effect origin, the use of positive country of origin effect had no significant influence in brand evaluation, however influenced the non-luxury brands. The negative country of origin effect influence both, but the effect is stronger in non-luxury brands. When the luxury brand advertisement did not mention the country of origin there was no relevant effect the brand evaluation, but influenced the non-luxury brands when compared with negative country of origin advertisements.